2018
DOI: 10.5230/jgc.2018.18.e7
|View full text |Cite
|
Sign up to set email alerts
|

Early Detection is Important to Reduce the Economic Burden of Gastric Cancer

Abstract: PurposeEarly detection of gastric cancer is important to improve prognosis. Early detection enables local treatment, such as endoscopic submucosal dissection (ESD). Therefore, we investigated whether early detection of gastric cancer could reduce healthcare costs by comparison according to stage and treatment modalities.Materials and MethodsMedical care costs were investigated according to tumor stage and initial treatment modality in 1,188 patients newly diagnosed with gastric cancer at 7 medical institutions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 17 publications
0
20
0
2
Order By: Relevance
“…Endoscopic resection, which preserves the entire stomach, improves the quality of life, causes lesser complications, requires a shorter hospital stay, and is more cost-effective than surgical resection. [93][94][95][96][97][98] In conclusion, we recommend endoscopic resection as the first line of treatment for well or moderately differentiated tubular or papillary gastric adenocarcinoma measuring ≤2 cm in diameter without endoscopic signs of ulcer and submucosal invasion since endoscopic resection is comparable to surgical resection in terms of survival, is associated with a satisfactory quality of life, and is economical. [93][94][95][96] Statement G4: We suggest endoscopic resection for early gastric cancer of well or moderately differentiated tubular or papillary adenocarcinoma with the following endoscopic findings: (1) mucosal cancer >2 cm without ulcer, or (2) mucosal cancer ≤3 cm with ulcer (Grade of recommendation: weak, Level of evidence: moderate).…”
Section: Statement G3: We Recommend Endoscopic Resection For Early Gamentioning
confidence: 98%
“…Endoscopic resection, which preserves the entire stomach, improves the quality of life, causes lesser complications, requires a shorter hospital stay, and is more cost-effective than surgical resection. [93][94][95][96][97][98] In conclusion, we recommend endoscopic resection as the first line of treatment for well or moderately differentiated tubular or papillary gastric adenocarcinoma measuring ≤2 cm in diameter without endoscopic signs of ulcer and submucosal invasion since endoscopic resection is comparable to surgical resection in terms of survival, is associated with a satisfactory quality of life, and is economical. [93][94][95][96] Statement G4: We suggest endoscopic resection for early gastric cancer of well or moderately differentiated tubular or papillary adenocarcinoma with the following endoscopic findings: (1) mucosal cancer >2 cm without ulcer, or (2) mucosal cancer ≤3 cm with ulcer (Grade of recommendation: weak, Level of evidence: moderate).…”
Section: Statement G3: We Recommend Endoscopic Resection For Early Gamentioning
confidence: 98%
“…According to the results of the 2015 China Cancer Statistics, released by the National Central Cancer Registry of China, the estimated incidence of GC in China is ~679,000 cases in 2015, second only to lung cancer (2). Epidemiological data has revealed that the 5-year survival rate is >90% for early-stage GC, with a poor prognosis observed for advanced GC cases (3). Therefore, improving the diagnostic rate of GC and its precancerous form is of great significance in the treatment and prognosis of GC.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 The lack of early diagnosis and effective therapy is the major reason for the deaths of GC patients, concomitant with the massive healthcare costs. [4][5][6] Hence, it is imperative to have a deep insight into the etiology of GC so as to discover some effective management strategies.…”
Section: Introductionmentioning
confidence: 99%